Position sensorless control for doubly salient electro‐magnetic motor based on line‐to‐line voltage. Issue 1 (12th September 2017) - Zhou, Xingwei; Zhou, Bo; Yang, Lan
Abstract : This study first proposes a novel position sensorless control method for doubly salient electro‐magnetic motor (DSEM) based on line‐to‐line voltage. The commutation instants are estimated by comparing the proper line‐to‐line voltage with a commutation threshold value, which is preset according to motor speed and field current. Since only line‐voltage is required, the negative influence of DSEM neutral point voltage variation is eliminated. Moreover in addition, line‐to‐line voltage has a gain of phase back‐electromotive force (EMF), so the application speed range is desired to be extended. Then, the sensorless commutation lags introduced by reluctance back EMFs and low‐pass filters are analysed in detail, with the obtained mathematic expressions, a uniform compensation strategy by adjusting the commutation threshold value is proposed. With no need for extra hardware, the compensation strategy has the merit of easy implementation. What is more, to overcome the restriction of the distorted commutation signal arising in freewheeling process, a constraint of three‐phase currents is developed to avoid false commutation. Finally, the experiments on a 12/8‐pole DSEM validate the correctness and feasibility of the proposed techniques.